Application of the New Jersey Department of Environmental Protection Water Budget Manual to Finderne Farms Wetland Mitigation and Assessment of Project Performance. (1st October 2013) - Messaros, Roy C.
Abstract : The U.S. Army Corps of Engineers, NY District's wetland mitigation proposal for Finderne Farms in Bridgewater, NJ, was approved in August 2005 by the state regulatory agency. The design goal was to provide mitigation for wetlands impacted by the Green Brook Flood Control project at a ratio of 2 : 1. As part of the design process in 2001, the available historical hydrologic data was evaluated. At that time, the NJ Department of Environmental Protection (NJDEP) Water Budget Manual was not available as a tool for accessing an acceptable design hydroperiod. Construction of the Finderne mitigation site was completed in July 2006. A six-year postconstruction monitoring program has determined that certain areas at the site have not achieved the established wetland success criteria. In 2012, there was a 28% survival of planted woody vegetation and a 74% cover of invasive species within Creation Area 1, a palustrine forested wetland. With the advent of the Water Budget Manual, a reevaluation of the historical hydrologic data was performed. Based on this analysis, the hydroperiod and soil moisture conditions are not representative of sustainable wetlands. Adaptive management measures are currently being developed and evaluated to improve the hydrology, hydric soil conditions, and survival of target vegetation at the Finderne site.